Zniesienie karalności łapownictwa czynnego jako element walki ze zjawiskami korupcyjnymi (art. 229 §6 k.k.) - Sowiński, Piotr Krzysztof (My University, 2015)
The Author analyzes the phenomenon of corruption and presents his views upon effective methods of fighting against this phenomenon. The subject literature lists three methods of counteracting. The first one includes creation of such legal norms that would limit discretion of public authority decisions and incohesion of law, as well as creation of internal and external control institutions to discover corruption, and the subsequent and accompanying punishing ofpersons who have been proved corruption (the punitive and administrative group). The second method consists in carrying out substantial economic reforms, liquidating conditions that welcome corruption. The third one aims at creation of a system that would be common for a specific community, rest on several complementary programmes and be implemented by independent subjects, on the one hand focusing on fight against corruption, and on the other on enhancing the quality of management, and directed towards “an increase in integrity” of the society. This text concerns the first of the described methods. In this context, the author has presented the solutions accepted in the penal code of 1997, basing on mitigation of criminal responsibility of a perpetrator of the act (Art. 229 §6) in exchange of the specified behaviour of the individual, consisting in informing the prosecution agencies of the fact that the said crime has been committed and disclosing all substantial circumstances of it.
PUNISHABILITY ABOLITION IN CASES OF ACTIVE BRIBERY AS AN ELEMENT OF FIGHT AGAINST CORRUPTION PHENOMENA (ART. 229 §6 OF CC)